1982 : Japanese Contemporary Art Exhibition. - Camden Arts Centre, London (Tokyo : Japan Art & Culture Association, 1982)
Ay-o ; Domoto, Hisao ; Enokura, Koji ; Kamiya, Shin ; Kawaguchi, Tatsuo ; Kimura, Kosuke ; Duck Jun Kwak ; Koshimizu, Susumu ; Ida, Syoichi ; Inumaki, Kenji ; etc.
1982 : Japanese Contemporary Art Exhibition, Camden Arts Centre, London, 27 January - 21 February 1982
boek